THE GUARANTEE OF SOCIAL NEEDS IN jaminan kebutuhan pokok dalam perspektif ekonomi Islam - Sutono Sutono (Sekolah Tinggi Pariwisata Mataram, 2021)
The guarantee of people's basic needs is a very important discussion in the context of religious pluralism in Indonesia. Understanding the meaning of guarantee for community needs is an attempt to know the systems and regulations that are promulgated by the Indonesian government with the rules and concepts of guaranteeing community needs based on the Shari'ah political economy policy on welfare that is accepted by the people in Indonesia. Therefore, this article aims to (1) Know the theory of human needs in society; (2) Analyzing the security needs of the community; (3) Analyzing the community's need assurance system in the perspective of shari'ah politics and economics with literature study. The results of the analysis show that (1) The theory and concept offered by Abraham Maslow is a basic offer of human needs in the welfare process (2) The accuracy and validity of the Indonesian government law in implementing the rules for social welfare security, there is still a little social inequality. (3) Offers the concept of social welfare for the people that was valid during the golden age and glory of Umar bin Khattab's government